Pembelajaran kewirausahaan berbasis hand made - Inanna Inanna; Rahmatullah Rahmatullah; Nurdiana Nurdiana (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The Community Partnership Program (PKM) partner is Al-Qalam Creative Community. The problem is: (1) the lack of knowledge and interest of the management in developing entrepreneurial spirit in the form of making hand-based crafts, (2) lack of skills to make hand made that has high competitiveness, (3) the quality of the production of kur rope bags that have very limited accessories. The external target is the kur strap bag which has a variety of colors for adults, teenagers, and children. The method used is: lectures, demonstrations, discussions, questions and answers, and counterpart partners. The results achieved are (1) partners have the knowledge in arranging kur strap into bags, (2) partners have the skills to design the shape of kur strap bags, (3) partners have the ability to increase the production of kur strap bags that have accessories with attractive appearance, and (4) partners have the ability to improve the quality of Kur strap bags with a variety of beautiful color variations.